Early Enteral Nutrition Adequacy Mitigates the Neutrophil–Lymphocyte Ratio Improving Clinical Outcomes in Critically Ill Surgical Patients. (10th September 2018) - Ortiz‐Reyes, Luis Alfonso; Chang, Yuchiao; Quraishi, Sadeq A.; Yu, Liyang; Kaafarani, Haytham; de Moya, Marc; King, David R.; Fagenholz, Peter; Velmahos, George; Yeh, Daniel Dante
Abstract: Background: Neutrophil–lymphocyte ratio (NLR) is a measure of host inflammatory response; a higher NLR is associated with worse clinical outcomes. Enteral nutrition (EN) may mitigate inflammation through interaction with gut‐associated lymphoid tissue. We hypothesized that early EN adequacy in critically ill surgical patients is associated with lower NLR and better clinical outcomes. Methods: In this retrospective study, we analyzed data from adult surgical intensive care unit (ICU) patients receiving EN. NLR at baseline ICU admission (NLR‐B), NLR after 3–5 days of EN (F‐NLR), nutrition adequacy, caloric deficit (CD), protein deficit (PD), hospital length of stay (LOS), ICU LOS, 28‐day ventilator‐free days (28‐VFD), and in‐hospital mortality were collected. Tertiles groups were created for NLR, F‐NLR, CD, and PD; the highest (H) and lowest (L) tertiles were compared. Regression analyses were performed to control for effect of age, gender, APACHE II, and NLR. Results: Subjects in the L‐CD group had lower median F‐NLR (7 [range, 5–11] vs 10 [7–22], P  = 0.005) and shorter ICU LOS (9 [6–16]) vs 16 [9–32] days; P  = 0.006). The L‐NLR group had shorter hospital LOS (18 [10–31] vs 22 [15–38] days, P  = 0.023), greater 28‐VFD (23 [18–25] vs 19 [11–22] days, P  = 0.005), and lower in‐hospital mortality (13% vs 41%, P  = 0.002). Conclusion: In critically ill surgical patients, early enteral caloric adequacy is associated with less inflammation and improved clinical outcomes.